Improved performance of surface functionalized TiO2/activated carbon for adsorption–photocatalytic reduction of Cr(VI) in aqueous solution. (November 2015) - Fu, Xiaofei; Yang, Hanpei; Lu, Guanghua; Tu, Yanmei; Wu, Junming
Abstract: TiO2 coated on activated carbon (TiO2 /AC) was synthesized by a facile sol-hydrothermal preparation. The as-prepared TiO2 /AC was modified by sequential treatment of nitric acid and thionyl chloride, followed by surface attaching of diethylenetriamine. The obtained materials were characterized by transmission electron microscopy, Fourier transform-infrared spectroscopy, X-ray photoelectron spectroscopy, X-ray diffraction, BET adsorption, and their adsorption–photocatalytic reduction activities were evaluated by the removal of aqueous Cr(VI). The results showed that TiO2 particles were homogeneously deposited on the surface of activated carbon, and diethylenetriamine was grafted covalently onto the surface of TiO2 /AC through amide linkage. The diethylenetriamine-functionalized TiO2 /AC (TiO2 /AC-DETA) exhibits high adsorption capability for Cr(VI) through electrostatic, coordinative and hydrogen bonding interactions. The significant enhancement of photocatalytic activity of TiO2 /AC-DETA for reduction of Cr(VI) was observed, which was mainly attributed to the enrichment of Cr(VI) onto the surface of AC and successive fast interfacial transfer of Cr(VI) and photogenerated electrons resulted from the intimate contact between AC and TiO2 through dense heterojunctions by forming of C–O–Ti linkages.